2001
DOI: 10.1381/09608920160556832
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Biliopancreatic Diversion for the Treatment of Morbid Obesity: Initial Experience

Abstract: The technique, with an acceptable level of complexity, can be safely executed by laparoscopy as described by Scopinaro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…Early results were published by a few centers (EL 4 [25,256,275,297,346]) and showed promising results in terms of technical feasibility and postoperative morbidity, but long-term data are lacking so far. The only comparative study (performed in superobese patients) found similar weight loss and reconvalescence after laparoscopic and open BPD, but better improvement of comorbidities in the laparoscopic group [165].…”
Section: Surgical Access: Open Vs Laparoscopicmentioning
confidence: 99%
“…Early results were published by a few centers (EL 4 [25,256,275,297,346]) and showed promising results in terms of technical feasibility and postoperative morbidity, but long-term data are lacking so far. The only comparative study (performed in superobese patients) found similar weight loss and reconvalescence after laparoscopic and open BPD, but better improvement of comorbidities in the laparoscopic group [165].…”
Section: Surgical Access: Open Vs Laparoscopicmentioning
confidence: 99%
“…In the early 1990s, Hess and Hess [2 ]and Marceau et al [3] performed a longitudinal gastric resection as a variation of the original Scopinaro type BPD with a horizontal gastrectomy [4], mainly to decrease the rate of anastomotic ulcers by preserving the pylorus and reduce the number of revisions. Paiva et al [5] performed the first LSG in 2000 in the context of the first laparoscopic BPD-DS (LBPD-DS). High early morbidity and mortality of LBPD-DS in patients with high BMI (>60) led to a staged concept with primary LSG to induce initial weight loss, followed either by laparoscopic Roux-en-Y gastric bypass (LRYGB) or LBPD-DS in case of insufficient weight loss [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the alimentary limb was 250 cm in length and the common channel was always 100 cm [50,51,56]. The first small series of laparoscopic BPD-DS was published by Paiva from Brazil in 2001 [57]. BPD-DS is in many bariatric centers a second-line operation in case of failure of mainly restrictive procedures (Fig.…”
Section: Laparoscopic Sleeve Gastrectomymentioning
confidence: 99%